2021
DOI: 10.1007/s12282-021-01232-1
|View full text |Cite
|
Sign up to set email alerts
|

Indices of peripheral leukocytes predict longer overall survival in breast cancer patients on eribulin in Japan

Abstract: Background It was reported that eribulin regulates the tumor microenvironment, including the immune system, by inducing vascular remodeling. Lymphocyte counts are a critical index of immune response in patients. The non-Asian, global EMBRACE study has suggested that baseline absolute lymphocyte count (ALC) may be a predictor of the survival benefit of eribulin in breast cancer patients. We examined whether the baseline ALC is a potential predictor of overall survival (OS) in Japanese patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…These data suggest pretreatment NLR may be a useful prognostic marker in the setting of HR+, HER2− advanced or metastatic breast cancer treated with abemaciclib but was not predictive of treatment response, as the benefit of abemaciclib was observed irrespective of baseline NLR. The current findings are broadly aligned with several recent meta-analyses that indicate baseline NLR correlates with disease-free survival and OS in a variety of breast cancer subtypes 41-43 , 47 , 48 and may be a general prognostic factor for PFS and OS in patients with metastatic breast cancer treated with eribulin, 29 , 30 , 32 with high NLR consistently associated with poorer prognosis.…”
Section: Discussionsupporting
confidence: 85%
“…These data suggest pretreatment NLR may be a useful prognostic marker in the setting of HR+, HER2− advanced or metastatic breast cancer treated with abemaciclib but was not predictive of treatment response, as the benefit of abemaciclib was observed irrespective of baseline NLR. The current findings are broadly aligned with several recent meta-analyses that indicate baseline NLR correlates with disease-free survival and OS in a variety of breast cancer subtypes 41-43 , 47 , 48 and may be a general prognostic factor for PFS and OS in patients with metastatic breast cancer treated with eribulin, 29 , 30 , 32 with high NLR consistently associated with poorer prognosis.…”
Section: Discussionsupporting
confidence: 85%
“…Other studies have reported that a high baseline ALC was associated with improved OS despite the use of different ALC cut-offs (e.g. 1000/µl, 1500/µl or the median ALC value) [ 4 6 , 8 ]. In the current study, a baseline ALC > 1000/µl was an independent predictor of OS, a finding consistent with previous studies [ 9 , 27 – 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These actions contribute to an improvement in OS in patients with A/MBC [ 18 ]. Several studies have shown that a high ALC or a low baseline NLR is associated with better survival outcomes in patients with A/MBC treated with eribulin [ 4 , 5 , 7 , 8 ], but not for patients receiving traditional treatments [ 3 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They identified a low baseline NLR (<3.0) as an independent predictive marker of durable clinical benefits and better PFS in patients with STS treated with eribulin ( Sato et al, 2021 ). NLR and absolute lymphocyte count are attracting attention as predictors of the effect of eribulin on metastatic breast cancer ( Miyagawa et al, 2018 , Miyoshi et al, 2020 , Takahashi et al, 2021 ). A combination of NLR and PLR has been reported to be able to predict survival in patients with STS ( Shimada et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%